Emotional Intelligence as a Predictor of Teaching Effectiveness and Professional Well-Being Among University Lecturers: A Cross-Sectional Study - Soyol-Erdene Sanjaa (Barkah Publishing, 2026)
Emotional intelligence (EI) has been linked to teaching effectiveness and well-being in school teachers, yet evidence in higher education remains fragmented. University lecturers face distinct professional demands that may render EI especially consequential for both instructional quality and personal psychological functioning. This study examined whether EI predicts teaching effectiveness and professional well-being among university lecturers, controlling for demographic and occupational covariates, and tested whether the four branches of the Mayer–Salovey–Caruso model exhibit differential predictive validity. A cross-sectional survey was administered to 178 university lecturers from four public and three private universities. EI was assessed with a validated short form of the Mayer–Salovey-Caruso Emotional Intelligence Test (MSCEIT). Teaching effectiveness was measured using the Teaching Effectiveness Inventory. Professional well-being was assessed with the PERMA-Profiler. Hierarchical multiple regression analyses were conducted, entering demographic and occupational characteristics in Step 1, total EI in Step 2, and MSCEIT branch scores in Step 3. Total EI explained an additional 18% of variance in teaching effectiveness (ΔR² = 0.18, β = 0.44, *p* < .001) and 23% of variance in professional well-being (ΔR² = 0.23, β = 0.50, *p* < .001) beyond covariates. In simultaneous branch analyses, strategic EI (Understanding and Managing Emotions) emerged as the strongest unique predictor of both outcomes, whereas Experiential EI (Perceiving and Using Emotions) did not reach significance when other branches were controlled. Lecturers in the highest teaching effectiveness quartile demonstrated significantly elevated profiles on the Understanding and Managing branches. EI, particularly the strategic branches involving reasoning about and regulating emotions, is a meaningful predictor of university lecturers’ teaching effectiveness and professional well-being. Findings support the conceptualization of EI as a malleable professional capacity and suggest targeted directions for faculty development interventions.